Analisis Soal Ujian Mata Pelajaran Bahasa Arab Kelas 12 di Madrasah Aliyyah - Iza Zainal Ambiya; Sopwan Mulyawan; Hasan Saefuloh (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2022)
Item analysis is a tool to find out whether the question is sufficient with a good question category or not.Â In addition, the purpose of item analysis is also to help improve the test through revision or removing ineffective questions, as well as to find out diagnostic information to students whether or not they have understood the material that has been taught.Â In this case, there are still a lot of student scores that are still below the KKM standard. There is no analysis of the problem so that one will not know whether the question is said to be a good question or not.Â Meanwhile, the teacher only corrects right and wrong.Â then not tested first for various reasons.Â That's why the researcher wanted to analyze the madrasa exam questions made by the teacher himself.Â In this research, the researcher uses quantitative descriptive method, which is a research that describes the data analysis in numbers. The researcher found that the relationship between questions and language skills included 2 language skills, namely: the ability to